The Role of Medical Social Work to Raise awareness of Prevention of The Epidemic Diseases - Ramadan AbdElhalim, Dr . Amal (International Journal of Scientific Research and Management (IJSRM), 2021)
Social work seen as important for preventing epidemic diseases, especially in times of crisis, however, evidence of this importance is still scarce, especially in the developing world. We addressed this by studying the role of medical social work in raising awareness of preventing epidemic diseases, and an analytical and descriptive cross-sectional study conducted among Saudi social workers and consumers (102). It aims at the extent to which the social worker knows the nature of epidemic diseases. And defining the preventive role of social workers in raising awareness of preventive diseases. The premise is that there is a significant reciprocal relationship between them. Non-probability fit sampling has been implemented; A self-administered questionnaire was developed during the COVID20 virus for the year 2020, it was tested and filled out by 102 male and female social workers, and the results showed that the total weights and percentage of the social worker’s knowledge of the dimensions of epidemic diseases are (3022), (89.70%) respectively and the role of the specialist Social awareness in raising awareness of the preventive disease dimension (3309), (83.2%), respectively, was associated with a strong positive correlation with compliance among respondents, in addition to the study's observation of the relationship between socio-demographic background and study dimensions T. Not significant at the 0.05 level (2 tailed) ( Age, experience, gender, marital status, and residence).